Agricultural water storage in an era of climate change: assessing need and effectiveness in Africa - McCartney, Matthew P.; Rebelo, Lisa-Maria; Xenarios, Stefanos; Smakhtin, Vladimir U. (International Water Management Institute, 2013)
By mitigating the vagaries of climate variability, agricultural water storage is widely anticipated to make a key contribution to climate change adaptation in Africa. However, if the planning of water storage is not improved, it is likely that many investments will fail to fully deliver intended benefits. This report describes the agricultural water storage continuum and some of the possible implications of climate change. A simple diagnostic tool which can be used to provide a rapid evaluation of the need and effectiveness of different water storage options, under existing and possible future climate conditions, is presented.